2022
DOI: 10.1111/1753-6405.13294
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for tobacco control in Australia: a qualitative study

Abstract: Objective: A greater understanding of the challenges and opportunities for tobacco control in Australia can assist with accelerating efforts in this space. This study sought to explore these challenges and identify priorities for policy and practice. Methods: Interviews were conducted with 31 individuals working in tobacco‐ and/or nicotine‐related research, policy and practice in Australia. Interviewees were tobacco control and cessation advocates, researchers, public servants and health practitioners represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These findings suggest that Australia's tobacco control efforts must be accelerated and that renewed attention to reduce smoking rates is urgently needed. Little has been done in relation to tobacco cigarette smoking since the introduction of plain packaging a decade ago, with experts calling for increased investment in measures such as national mass media campaigns, updated warnings on tobacco packaging, and the expansion of smoke-free areas 25 . These measures serve to denormalize smoking and have been found to be effective at reducing smoking initiation among adolescents 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that Australia's tobacco control efforts must be accelerated and that renewed attention to reduce smoking rates is urgently needed. Little has been done in relation to tobacco cigarette smoking since the introduction of plain packaging a decade ago, with experts calling for increased investment in measures such as national mass media campaigns, updated warnings on tobacco packaging, and the expansion of smoke-free areas 25 . These measures serve to denormalize smoking and have been found to be effective at reducing smoking initiation among adolescents 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…17 A qualitative study on the views of selected individuals working in tobacco control in Australia suggested conventional policy measures, rather than endgame approaches, remain the focus. 21 Given that the current rate of decline is insufficient to reach the goal of <5% smoking prevalence, 22 and current approaches are unlikely to achieve equity for populations with high smoking prevalence, additional support is required to progress policies that could achieve this national goal.…”
Section: Original Researchmentioning
confidence: 99%
“…Australia is known as one of the world’s leading nations in tobacco control. It has one of the lowest smoking rates worldwide, with just 11.2% of people aged 14 years and over reporting daily smoking in 2020-21 [ 1 , 2 ]. This success has been attributed to the implementation of tobacco control policies such as smoke-free laws, anti-smoking mass media campaigns, graphic health warnings, regular increases in tobacco taxes, bans on advertisement and promotional materials, and the introduction of plain packaging [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has one of the lowest smoking rates worldwide, with just 11.2% of people aged 14 years and over reporting daily smoking in 2020-21 [ 1 , 2 ]. This success has been attributed to the implementation of tobacco control policies such as smoke-free laws, anti-smoking mass media campaigns, graphic health warnings, regular increases in tobacco taxes, bans on advertisement and promotional materials, and the introduction of plain packaging [ 2 , 3 ]. From September 2011, nicotine products other than transdermal or oromucosal use have been classified as prescription only (Schedule 4) medicines for human therapeutic use and as dangerous poisons (Schedule 7) for non-therapeutic use in the Poisons Standard of the Therapeutic Goods Administration (TGA) [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%